Dynamic conductivity of one-dimensional ion conductors. Impedance, Nyquist diagrams - Stasyuk, I.V.; Stetsiv, R.Ya. (Condensed Matter Physics, 2016)
Dynamic conductivity of the one-dimensional ion conductor is investigated at different values of the interaction
constant between particles and the modulating field. The consideration is based on the hard-core boson lattice
model. Calculations are performed for finite one-dimensional cluster using the exact diagonalization method.
Frequency dependence of the dynamic conductivity and behaviour of its static component (Drude weight) in
the charge-density-wave (CDW) and superfluid (SF) phases are studied. Frequency dispersion of impedance and
loss tangent is calculated; the Nyquist diagrams are built and analyzed. Дослiджено залежнiсть динамiчної провiдностi одновимiрного iонного провiдника в залежностi вiд величини взаємодiї мiж частинками i величини модулюючого поля. Розгляд базується на гратковiй моделi
жорстких бозонiв. Розрахунки проведено методом точної дiагоналiзацiї для скiнченного одновимiрного кластера. Вивчається частотна залежнiсть динамiчної провiдностi i поведiнка її статичної складової
(внеску Друде) в зарядовпорядкованiй фазi (CDW) i в фазi типу суперфлюїду (SF). Розраховано частотну
дисперсiю iмпедансу i тангенса втрат; побудовано дiаграми Найквiста.